Perkembangan Sastra Indonesia dari Budaya Lisan Ke Karya Tulis Modern - Nasyitha Rizqiya (Lembaga Pengembangan Kinerja Dosen, 2024)
This article discusses the role and transformation of oral culture in Indonesia, which has existed since prehistoric times, as a means of conveying values, knowledge, and community identity. Along with the development of the times and technological advances, oral traditions face various challenges, especially due to the influence of foreign cultures and the dominance of digital media. However, oral culture still has high relevance and has the potential to be preserved through digital media, which opens up opportunities for traditional literary works to be adapted into more modern forms of writing. Through a qualitative approach and literature studies, this article explores the importance of oral tradition in people's lives and its contribution to the development of Indonesian literature, as well as how the internet era and digital technology changed the way it was preserved and spread.